Epidemiology of gastrostomy insertion for children and adolescents with intellectual disability - Wong, K.; Leonard, H.; Pearson, G.; Glasson, E.J.; Forbes, D.; Ravikumara, M.; Jacoby, P.; Bourke, J.; Srasuebkul, P.; Trollor, J.; Wilson, A.; Nagarajan, L.; et al. (SPRINGER, 2019)
The largest group of recipients of pediatric gastrostomy have neurological impairment with intellectual disability (ID). This study investigated trends in first gastrostomy insertion according to markers of disadvantage and ID etiology. Linked administrative and health data collected over a 32-year study period (1983–2014) for children with ID born between 1983 and 2009 in Western Australia were examined. The annual incidence rate change over calendar year was calculated for all children and according to socioeconomic status, geographical remoteness, and Aboriginality. The most likely causes of ID were identified using available diagnosis codes in the linked data set. Of 11,729 children with ID, 325 (2.8%) received a first gastrostomy within the study period. The incidence rate was highest in the 0–2 age group and there was an increasing incidence trend with calendar time for each age group under 6 years of age. This rate change was greatest in children from the lowest socioeconomic status quintile, who lived in regional/remote areas or who were Aboriginal. The two largest identified groups of ID were genetically caused syndromes (15.1%) and neonatal encephalopathy (14.8%). Conclusion: Gastrostomy is increasingly used in multiple neurological conditions associated with ID, with no apparent accessibility barriers in terms of socioeconomic status, remoteness, or Aboriginality.What is Known:• The use of gastrostomy insertion in pediatrics is increasing and the most common recipients during childhood have neurological impairment, most of whom also have intellectual disability (ID).What is New:• Nearly 3% of children with ID had gastrostomy insertion performed, with the highest incidence in children under 3 years of age.• Gastrostomy use across different social groups was equitable in the Australian setting.